Intersectional Identity Studies in Colombian ELT: A Profiling Research Study - Catherine Benavides-Buitrago (Asociación Colombiana de Profesores de Ingles, 2023)
This article aims at sharing the preliminary literature review of the main developments related to Intersectional Identities in Colombian English Language Teaching and general educational contexts worldwide. First, I trace the research work concerning the topic at both national and international levels through a bibliometric analysis in Scopus to see the main developments regarding intersectionality from a decolonial perspective. Then, I show through a complementary bibliometric study, 50 articles that were collected from different databases, and the trends found as representation of intersectional studies. The analysis indicates two core trends: (1) Intersectional studies in general educational contexts and (2) Intersectional studies in ELT contexts. Finally, I present how this profiling research study shows that the topic of Intersectional Identities in Colombia seems scarce within the field of ELT.